2020
DOI: 10.1155/2020/8886955
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 Induces Apoptotic Cell Death in Triple‐Negative Breast Cancer Cell Lines and Prevents Carcinogen‐Induced Breast Tumorigenesis in Sprague Dawley Rats

Abstract: The objective of this study is to investigate the anticancer potential of ginsenoside Rg1 using in vitro and in vivo experimental models. In this study, we found that ginsenoside Rg1 induces cytotoxicity and apoptotic cell death through reactive oxygen species (ROS) generation and alterations in mitochondrial membrane potential (MMP) in the triple-negative breast cancer cells (MDA-MB-MD-231 cell lines). We found that ginsenoside Rg1 induces the formation of gamma H2AX foci, an indication of DNA damage, and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…The animals were palpated regularly to assess the changes in the mammary tissue. The number of death and the time of death in each group were reported [22][23][24][25].…”
Section: Experimental Designmentioning
confidence: 99%
“…The animals were palpated regularly to assess the changes in the mammary tissue. The number of death and the time of death in each group were reported [22][23][24][25].…”
Section: Experimental Designmentioning
confidence: 99%
“…Ginsenoside Rg1 (C 42 H 72 O 14 , Rg1, Figure 1A ) is one of the bioactive constituents of ginseng ( 17 ). Rg1 has strong pharmacological activity and has been discovered to have a beneficial effect on the treatment of various diseases, such as obesity ( 18 ), type 2 diabetes ( 19 ), nonalcoholic fatty liver ( 20 ), cancer ( 21 ), hyperlipidemia ( 22 ), acute lung injury ( 23 ), nephritis ( 24 ), and arthritis ( 25 ). A wide range of studies has disclosed the pharmacological effect of Rg1 on UC ( 17 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ginsenoside Rg1 Ginsenoside Rg1 is an effective anti-cancer component in total ginsenosides ( Li J. et al, 2014 ). It is reported that ginsenoside Rg1 decreases cell viability, inhibits cell proliferation, induces reactive oxygen species (ROS) thereby drives apoptosis of BC cells ( Chu et al, 2020 ). In details, ginsenoside Rg1 induces apoptosis by generating ROS of BC cells ( Chu et al, 2020 ).…”
Section: Anti-breast Cancer Activity Of Ginsenosidesmentioning
confidence: 99%